Sosialisasi dan Pelatihan Penggunaan Platform Digital untuk Literasi Hukum Kesehatan: Inovasi Edukasi Hak Anak dalam Pencegahan Stunting di Wilayah Perbatasan Indonesia–Papua Nugini - Klau, Ricardo Goncalves; Fahmi, Mohammad Saiful; Buono, Lintang Cahyo; Enala, Syahrabudin Husein (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
A community service activity entitled socialization and training on the use of digital platforms for health legal literacy: innovation in child rights education in stunting prevention in the indonesia-papua new guinea border area was held on november 1-3, 2025, in kweel village, eligobel district, merauke regency, south papua. This activity was motivated by the low legal and health literacy of border communities, particularly regarding children's rights, nutrition, and stunting prevention. The program's objective was to improve children's health legal knowledge and digital skills in accessing and disseminating educational information. Implementation methods included health law socialization, training on the use of digital platforms, and community mentoring in family and school environments. Participants included teachers, community leaders, and youth from Kweel Village. Evaluation results showed an average increase of 35% in understanding of children's health legal matters and 40% in the ability to utilize digital platforms. This program supports the achievement of SDGs 3, 4, and 16 and contributes to IKU 2 and IKU 3 of higher education through the involvement of lecturers and students in real-impact activities.